04.01 Doings and dealings in synovitis: fibroblast-like synoviocyte cell-to-cell organelle transfer is directed by the inflammatory microenvironment. (1st March 2017) - Byrne, Ruth A; Calvo, Isabel Olmos; Kartnig, Felix; Karonitsch, Thomas; Steiner, Günter; Holinka, Johannes; Ertl, Peter; Smolen, Josef S; Kiener, Hans P
Abstract : Background: Fibroblast-like synoviocytes (FLS) form a complex tissue network via long-distance intercellular connexions with wide intercellular matrix spaces. The adaptive synovial tissue response to inflammation likely depends upon the concerted activity of FLS. Using an in-vitro synovial organ culture system, we explore mechanisms of FLS directed cellular cooperation. Methods: Human FLS were prepared from synovial tissues obtained as discarded specimens following joint arthroplasty. Cells were labelled with cell tracker dyes or specific organelle dyes and cultured in spherical matrigel micromasses. For selected experiments, micromasses were challenged with TNF or IFNγ. Data was acquired by confocal live cell imaging. Analysis of the resulting 4D movies was done using Imaris software. Results: To examine whether FLS transfer cytoplasmic cargo, we labelled 50% of FLS with green cell tracker dye and the other 50% with Mitotracker. Over time, red labelled organelles accumulated in green labelled cells with a transfer rate of 10% of newly affected cells/day. Confocal live cell imaging revealed that FLS indeed use their long-distance intercellular connexions for transfer of organelles. When micromasses were stimulated with TNF (10 ng/ml) the transfer rate increased by 2-fold when compared to control. By contrast, INFγ-stimulation resulted in decreased organelle transfer. The combined treatment of micromasses with TNF and IFNg, however, increased the transfer rate to a level beyond stimulation with TNF alone. Conclusions: Our experiments suggest transfer of cytoplasmic cargo, including organelles such as mitochondria between FLS. As transfer is distinctly regulated by the cytokine milieu, organelle transfer seems to be part of the adaptive synovial response to inflammation. These studies may provide insight into how synoviocytes orchestrate their activity. Further studies will demonstrate the significance of directed cargo exchange for the function of the normal as well as the diseased synovium.